Rare Case of Strongyloides stercoralis Hyperinfection in a Greek Patient with Chronic Eosinophilia - Kechagia, Maria (Medknow Publications & Media Pvt Ltd, 2012)
Strongyloidiasis is a disease characterized by a diverse spectrum of unspecific manifestations that complicate its diagnosis. Although, the course of its chronic form is usually benign, in cases of immunosuppression, iatrogenic or not, it can evolve to a hyperifection syndrome with even fatal complications. Herein, we report a case of Strongyloides stercoralis hyperinfection in a Greek patient receiving corticosteroid treatment for chronic eosinophilia and angioedema. The case represents an extremely rare case of autochthonous strongyloidiasis in Greece and underlines the importance of the early diagnosis of the disease's uncomplicated forms in order to prevent its severe sequelae.